Investigative journalism and the South African government: publishing strategies of newspaper editors from Muldergate to the present - Steyn, Nantie (My University, 2012)
The relationship between governments and the media has historically been an antagonistic one, and investigative journalism – the material manifestation of the role of the press as fourth estate – is central to this antagonism. In their capacity as the fourth estate, those newspapers that pursue and publish investigative journalism stand in opposition to government. Governments have responded to this opposition in a variety of ways; mostly, however, by way of legislated censorship of the press. In South Africa, the legislation that regulated what newspapers could print under apartheid was unusually vast. In spite of this, major exposés of government corruption – and worse – were seen on the front pages of those publications that pursue investigations into political malfeasance. In South Africa’s post-apartheid democracy, with constitutional protection of the freedom of expression, there has been increasing evidence of what Jackson has called the “embedded qualities of intolerance and secrecy” (1993: 164) in the state’s response to revelations of corruption in the press, culminating in the Protection of State Information Bill that was passed in Parliament in November 2011. The passing of the Bill has resulted in widespread concern about the possibility of legislated, apartheid-style censorship of the media and freedom of expression. I interviewed five editors who were part of exposing state corruption during and after apartheid, in order to establish what motivates their decisions to keep on printing stories that brings them into conflict with the political powers of the day, in spite of the financial consequences for their publications. Regardless of the different political landscapes, the strategies that they followed in order to keep on publishing were remarkably similar, as is their reason for continuing to publish investigative stories: they believe it embodies the role of the press in a democracy. Indicators are that editors will keep on publishing, in spite of attempts by the government to gag the press.
M.A. University of the Witwatersrand, Faculty of Humanities (Journalism and Media Studies), 2012
Keywords: Journalism--South Africa; Reporters and reporting; Newspapers--South Africa; Freedom of the press; Press and politics--South Africa; Government, Resistance to--South Africa; Investigative reporting